Training Methods to Improve Basketball Skills: The Impact of Basketball Specific Training on Speed, Agility, and Quickness Improvement in Male Basketball Players (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The aim of the present examination was to discover the impact of basketball particular training and traditional strategy for training on Speed-Agility-Quickness of NationalInteruniversityState level Basketball players. They were haphazardly allotted into three groups similarly. The three groups were named as pursues, the SAQE group-1, group-II named as the SAQNE and Active control (AC) - III. After finishing of the pre test, the subjects were treated with their particular training program. Training period was planned for seven weeks. Speed-agility-quickness - I (SAQE) experienced a basketball particular training program. Following seven weeks of the training time frame post test was led on the dependent variables of performance Ability for all the three groups. To dissect the treatment impact of training Mean and SD was utilized. To analyze the hugeness of mean contrasts among all the three groups investigation of covariance was utilized. It was inferred that the ramifications of multi parts training program particular to the basketball game may have been the wellspring of its predominance on the change of speed-agility-quickness of the male basketball players.